The judicial resolution of the tension between human rights treaties and shari’a law reservations under the constitution of 2014 - Moussa, Ali (AUC Knowledge Fountain, 2018)
The thesis explores the path of ratified human rights treaties in the Egyptian legal system. Although these treaties have the force of law, as mandated by the constitution, the examination of court practice in Egypt shows plenty of cases where the ratified treaties have been judicially discarded due to the conflict with domestic laws or the inconsistency with the rulings of Shari’a law. The thesis examines the judicial phenomenon of overthrowing ratified human rights treaties under the Egyptian constitutional provisions. In order to grasp the foundation of this phenomenon, the thesis studies the rules which regulate the formulation of reservations under the Vienna Convention on the Law of Treaties, Egypt’s position towards the application of international law on the domestic level, and the interpretation of Shari’a law. The thesis presents three examples of cases where the conflict between ratified human rights treaties, domestic laws, and Shari’a law reservations arise. The thesis demonstrates how the courts’ judgments resolved the conflict, and that the resolution upheld the application of domestic law and overthrew the ratified human rights treaties. Whereas the discussed judgements were made under the former constitutions, the paper investigates the judicial application of ratified human rights treaties under the provisions of the Constitution of 2014. The paper analyzes the novel provisions introduced to the Constitution of 2014 which are related to the application of human rights treaties. Based on these provisions, the paper argues that the constitution of 2014 opens the door for further judicial application of ratified human rights treaties.